1996
DOI: 10.1111/j.1460-9568.1996.tb01207.x
|View full text |Cite
|
Sign up to set email alerts
|

Colocalization of Oestrogen Receptor lmmunoreactivity and Preproenkephalin mRNA Expression to Neurons in the Superficial Laminae of the Spinal and Medullary Dorsal Horn of Rats

Abstract: A double-labelling procedure combining immunohistochemical staining with in situ hybridization using a radiolabelled cRNA probe was employed to demonstrate oestrogen receptor-like immunoreactivity and preproenkephalin-A mRNA in the medullary and spinal dorsal horn of female rats. Both markers labelled large numbers of neurons in the substantia gelatinosa and its trigeminal homologue. Many of these neurons were double-labelled, displaying both oestrogen receptor-like-immunoreactivity and preproenkephalin-A mRNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
64
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 97 publications
(69 citation statements)
references
References 29 publications
5
64
0
Order By: Relevance
“…There are a number of possible molecular mechanisms via which estrogen might diminish OFQ-induced antinociception, including decreasing the expression of the ORL 1 receptor (Flores et al, 2003) and/or its coupling to G-proteins (for review, see Kelly and Wagner, 1999;Malyala et al, 2005), which would secondarily modify the affinity of OFQ to the ORL 1 receptor. Estrogen receptors (ER␣/ER␤) are present in spinal dorsal horn neurons (Amandusson et al, 1996(Amandusson et al, , 1999Shughrue et al, 1997), and estrogen, in addition to altering the expression of opioid peptides (Medina et al, 1993;Micevych et al, 1997;Amandusson et al, 1999;Micevych and Sinchak, 2001) (for review, see Craft et al, 2004), has also been shown by us and others to alter the expression of the ORL 1 receptor gene and protein in the trigeminal region and the hypothalamus (Sinchak et al, 1997;Flores et al, 2003;Sinchak et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…There are a number of possible molecular mechanisms via which estrogen might diminish OFQ-induced antinociception, including decreasing the expression of the ORL 1 receptor (Flores et al, 2003) and/or its coupling to G-proteins (for review, see Kelly and Wagner, 1999;Malyala et al, 2005), which would secondarily modify the affinity of OFQ to the ORL 1 receptor. Estrogen receptors (ER␣/ER␤) are present in spinal dorsal horn neurons (Amandusson et al, 1996(Amandusson et al, , 1999Shughrue et al, 1997), and estrogen, in addition to altering the expression of opioid peptides (Medina et al, 1993;Micevych et al, 1997;Amandusson et al, 1999;Micevych and Sinchak, 2001) (for review, see Craft et al, 2004), has also been shown by us and others to alter the expression of the ORL 1 receptor gene and protein in the trigeminal region and the hypothalamus (Sinchak et al, 1997;Flores et al, 2003;Sinchak et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4]6,9,29 Nevertheless, the underlying networks are complex and the results of studies on hormonal pain modulation in humans, particularly those using laboratory induced pain, 14 remain notoriously diverse. 5,19,20,24,25,34,39,41 The clinical studies performed are generally based on a hormonal replacement therapy regimen.…”
Section: Discussionmentioning
confidence: 99%
“…This set-up thus offers the possibility to study pain perception in relation to extreme changes in estradiol levels in the same individual. 4 While responses to some pain stimuli have been examined during IVF treatment previously, 31,43 we here provide data from a comprehensive sensory testing protocol that examines different thin fiber modalities. We have employed a within-subject design to evaluate thresholds and tolerance to acute thermal pain, to pressure pain, and to tonic cold pain, at very low and very high serum levels of estradiol.…”
Section: Introductionmentioning
confidence: 99%
“…Few previous studies demonstrate less pain sensitivity during phases of the menstrual cycle associated with high estrogen which is reported by Hellstrom and Anderberg. [22] Amandusson et al reported that few estrogen receptor-expressing neurons are opioidergic [14] and show increased opioid transcription after taking estrogen. [23] One previous research study also reported the ovarian sex steroid antinociception as being mediated by opioid like mechanism and this might be due to activation of similar receptors in spinal cord.…”
Section: Discussionmentioning
confidence: 99%
“…[ [12][13][14] The female reproductive hormones have been reported to affect cardiovascular system in various ways, during the normal menstrual cycle. [15][16][17][18][19] The definitive interaction of these physiological characteristics is very meagerly found in literature search, particularly in young Indian females.…”
mentioning
confidence: 99%